Channels of Iranian pastoral nomads on the YouTube network: Video narratives of the life of the Lori (Lur) Bakhtiari tribal people and ethnic group - Gorunović Gordana (Glasnik Etnografskog Instituta SANU)
This paper is based on a qualitative analysis of the content of video narratives on YouTube channels of the so-called Iranian nomads from the Lor Bakhtiari ethnic group. The main question underlying the research is what an anthropologist as a viewer and an impartial bystander can learn from these amateur videoformats, which can be included in the genre of domestic folk films about the daily life and customs of the pastoral, partially sedentarized, (semi)nomads in southwest Iran. This way of documenting the daily practices of nomadic families and clans is primarily an alternative way of making money on YouTube, but it is also an ethnocultural promotion of the Lor Bakhtiari ethnic and tribal group and a tourist advertisement of their homeland - mountain villages and seasonal camps in the Zagros region, Lordegan district and Chaharmahal and Bakhtiari province. Observing the films of Iranian videographers who themselves belong to the culture of Lor Bakhtiari was the reason for the anthropologist to start getting acquainted with academic ethnology and anthropology in Iran, which belongs to those national traditions of the discipline that are located on the periphery of the world’s main, predominantly Western, centers of socio-cultural anthropology.